HbA1c and height loss among Japanese workers: A retrospective study - Shimizu, Yuji; Hayakawa, Hidenobu; Honda, Eiko; Sasaki, Nagisa; Takada, Midori; Okada, Takeo; Ohira, Tetsuya; Kiyama, Masahiko (PloS one, 2023)
Evaluating the risk of height loss could be an efficient way to evaluate endothelial health, which might be associated with all-cause and cardiovascular mortality. Diabetes is an established risk factor both for intervertebral disk degeneration and osteoporosis-related fractures, which are major risk factors for height loss among adults. Therefore, hemoglobin A1c (HbA1c), as an indicator of the presence of diabetes, could be positively associated with height loss. A retrospective study of 10,333 workers aged 40 to 74 years was conducted. Height loss was defined as being in the highest quintile of height decrease per year. HbA1c in the normal range was positively associated with height loss. The known cardiovascular risk factors-adjusted odds ratio (OR) and 95% confidence interval (CI) for height loss with a 1-standard deviation (SD) increase in HbA1c (0.38% for both men and women) was 1.06 (1.02, 1.10) for men and 1.15 (1.07, 1.23) for women, respectively. When limit those analysis among those without diabetes, the magnitude was slightly higher; the fully adjusted OR and 95% CI for height loss with a 1-SD increase in HbA1c was 1.19 (1.11, 1.28) for men and 1.32 (1.20, 1.44) for women, respectively. Even when HbA1c is within the normal range, higher HbA1c is a significant risk factor for height loss among workers.